PENGARUH SISTEM REKRUTMEN DAN PENGEMBANGAN KARYAWAN TERHADAP KINERJA KARYAWAN PADA PT. PANDU SIWI SENTOSA - Yasmina Martini; Hasyunah Hasyunah (Fakultas Ekonomi Universitas Tridinanti Palembang, 2022)
This research basically discusses how the influence of employee recruitment and development systems on employee performance at PT. Pandu Siwi Sentosa Palembang. Here the author tries to find out the influence of the Recruitment System and Employee Development as an independent variable which will be examined how it influences employee performance both simultaneously and partially.After conducting a literature review and preparing hypotheses, data were obtained from distributing questionnaires to 30 employees of PT. Pandu Siwi Sentosa Palembang, then analyzed the data obtained using quantitative data analysis. Quantitative analysis includes validity and reliability tests, Normality Test, multiple regression analysis, hypothesis testing through the f test and t test, as well as analysis of the correlation coefficient (r) and the coefficient of determination (R2).The results of this study obtained the influence of the Recruitment System and Employee Development simultaneously (f) on Employee Performance at PT. Pandu Siwi Sentosa Palembang. With the multiple linear regression equation, namely Y=2.915+0.583X1+0.888X2+e. Recruitment System and Employee Development Variables have a positive direction of the coefficient on Employee Performance at PT. Pandu Siwi Sentosa Palembang. The coefficient of determination is 0.854 or 85.4%, the performance variable can be explained or there is an influence on the Employee Recruitment and Development System variable, while the remaining 14.6% is influenced by other factors not examined in this study.Keywords: Recruitment System, Employee Development, and Performance